One of the major challenges of masking the bitter taste in medications: an overview of quantitative methods for bitterness - Wang, Panpan; Li, Haiyang; Wang, Yanli; Dong, Fengyu; Li, Han; Gui, Xinjing; Ren, Yanna; Gao, Xiaojie; Li, Xuelin; Liu, Ruixin (Frontiers in Chemistry, 2024)
The aim of the present study was to carry out a systematic research on bitterness quantification to provide a reference for scholars and pharmaceutical developers to carry out drug taste masking research. Significance: The bitterness of medications poses a significant concern for clinicians and patients. Scientifically measuring the intensity of drug bitterness is pivotal for enhancing drug palatability and broadening their clinical utility. Methods: The current study was carried out by conducting a systematic literature review that identified relevant papers from indexed databases. Numerous studies and research are cited and quoted in this article to summarize the features, strengths, and applicability of quantitative bitterness assessment methods. Results: In our research, we systematically outlined the classification and key advancements in quantitative research methods for assessing drug bitterness, including. These methods primarily encompassed in vivo quantification techniques such as traditional human taste panel methods, as well as in vitro quantification methods such as electronic tongue analysis. At the same time, we It focused on the quantitative methods and difficulties of bitterness of natural drugs with complex system characteristics and their difficulties in quantification, and proposes possible future research directions.. Conclusions: The quantitative methods of bitterness were summarized, which laid an important foundation for the construction of a comprehensive bitterness quantification standard system and the formulation of accurate, efficient and rich taste masking strategies.